(untitled) (Revista de História Regional, 2025)
The article analyzes the emergence of the first sports institutions in Talca at the beginning of the twentieth century. Marked by the context of modernization, sports clubs became an alternative to leisure and at the same time made possible new forms of socialization among members of civil society. It is postulated that the process of sports articulation allowed the deepening of social relations in Talca and contributed to reinforcing the liberal ideals and values of the period, which in turn allowed the strengthening of a local and national identity. Likewise, a recognition of the first organizations that were part of the foundational period of sports in Talca was generated. In methodological terms, the local press La Mañana and the sports magazines El Sport Ilustrado, La Revista Sportiva and Sport I Actualidades were used.